Impact of person-centered care training and person-centered activities on quality of life, agitation and antipsychotic use in people with dementia living in nursing homes: a cluster-randomized controlled trial of the WHELD intervention - Ballard, Clive; Corbett, Anne; Orrell, Martin; Williams, Gareth; Moniz-Cook, Esme; Romeo, Renee; Woods, Bob; Garrod, Lucy; Testad, Ingelin; Woodward-Carlton, Barbara; Wenborn, Jennifer; Knapp, Martin; et al. (Public Library of Science, 2018)
Background: Agitation is a common, distressing and challenging symptom affecting large numbers of people with dementia and impacting significantly on quality of life (QoL). There is an urgent need for evidence-based, cost-effective psychosocial intervention to improve these outcomes, particularly in the absence of safe, effective pharmacological therapies. This study aimed to conduct a large and rigorous RCT to evaluate the efficacy of a person-centered care and psychosocial intervention (WHELD) on QoL, agitation and antipsychotic use in people with dementia living in nursing homes, and to determine the cost of the intervention. Methods and Findings: This was a randomized controlled cluster trial comparing the WHELD intervention with treatment as usual in people with dementia living in 69 UK nursing homes, using an intention to treat analysis. All nursing homes allocated to the WHELD intervention received staff training in person-centered care (PCC), social interaction (SoI) and education regarding antipsychotic medications (AM) followed by ongoing delivery through a care staff champion model. The primary outcome measure was QoL (DEMQOL-proxy). Key secondary outcomes were agitation (Cohen Mansfield Agitation Inventory), neuropsychiatric symptoms (NPI) and antipsychotic use. Other secondary outcome measures were global deterioration (CDR), mood (Cornell Scale for Depression in Dementia CSSD), unmet needs (Camberwell Assessment of Need in the Elderly -CANE), mortality, quality of interactions (Quality of Interactions Scale -QUIS), pain (Abbey pain scale) and cost. Intervention costs were calculated using published cost function figures and compared with usual costs. 847 people were randomized to WHELD or treatment as usual, of whom 553 completed the nine month RCT. The WHELD intervention conferred a statistically significant improvement in QoL compared to treatment as usual over nine months (DEMQOL proxy z score 2.82, p=0.0042, Mean Difference 2.54 SEM 0.88, 95% Confidence Intervals (CI) 0.81, 4.28, Cohen's D 0.24). There was also statisticallya significant benefits in agitation (CMAI Z score 2.68 p=0.0076, Mean Difference 4.27 SEM 1.59, 95% CI -7.39, -1.15, Cohen's D 0.23) and in overall neuropsychiatric symptoms (Z score 3.52 Mean Difference 4.55 SEM 1.28 p=0.00045, 95% CI -7.07,-2.02, Cohen's D 0.30). The benefits were greatest in people with moderate-moderately severe dementia. There was also a statistically significant benefit in positive care interactions as measured by QUIS (19.7% increase, SEM 8.94, 95% CI 2.12, 37.16, Cohen's D 0.55, P=0.03). There were no statistically significant differences between the WHELD intervention and treatment as usual for the other secondary outcomes. A sensitivity analysis using a pre-specified imputation model confirmed statistically significant benefits in DEMQOL proxy, and CMAI and NPI with the WHELD intervention compared to treatment as usual. Antipsychotic drug prescribing was at a low stable level in both treatment groups across the study and the WHELD treatment intervention did not reduce antipsychotic use. The WHELD intervention reduced cost compared to treatment as usual, and the benefits achieved were therefore associated with a cost saving. The main limitation was that antipsychotic review was based on augmenting processes within care homes to trigger medical review and did not in this study involve proactive primary care education. The high mortality rate leading to non-completion in a significant proportion of participants leads to interpretation challenges for this study and for all long term intervention studies in nursing homes. Conclusions These findings suggest that this staff training and non-pharmacological intervention for people with dementia living in nursing homes may be able to achieve benefits to QoL, agitation and neuropsychiatric symptoms, as well as cost saving in a model that can readily be implemented into nursing homes. The benefits in QoL, agitation and neuropsychiatric symptoms had a small effect size. The benefits to agitation and neuropsychiatric symptoms are comparable to (agitation) or better than (NPI) the benefits seen with antipsychotic drugs. Importantly, the benefits were achieved in the context of a cost saving and used a model that can readily be implemented into nursing homes.